If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(2t+11)=-9(t+2)
We move all terms to the left:
-(2t+11)-(-9(t+2))=0
We get rid of parentheses
-2t-(-9(t+2))-11=0
We calculate terms in parentheses: -(-9(t+2)), so:We get rid of parentheses
-9(t+2)
We multiply parentheses
-9t-18
Back to the equation:
-(-9t-18)
-2t+9t+18-11=0
We add all the numbers together, and all the variables
7t+7=0
We move all terms containing t to the left, all other terms to the right
7t=-7
t=-7/7
t=-1
| a6=102 | | 4=5(x-6) | | 13t-3t=10 | | x3+-3=1 | | -6=-13k+11k | | -58=(.5)(9.8)t^2 | | x+8.92=9.235 | | y=10+0.4 | | 2(1/3t3)=1 | | 5x-3(2x-7)=-12+4(x-3) | | (9x-15)=(4x+24) | | 8p/2p=4p | | 78+x=43.2 | | 3x+-3=1 | | $2x-9=5x-33$ | | 23x+4=104+3x | | 3(x+7)²-17=25 | | -7(2n+5)-5=89 | | 11m=-12 | | 25=k/30 | | 2x+10+3x-5+2x+10+3x-5=40 | | x-85=231 | | 8u+4=9u+9 | | x-14=19* | | 5x+5+3x+1=180 | | 11x7x=39 | | (6r+7=13+7r) | | p(8)=4(8) | | 9•(-1•x)=9•(-x) | | 2x+4=2x-19 | | 2x-4(x-2)=-6+5x-7 | | -4=w/5+6 |